184 Effects of The Coronavirus Pandemic on Medical and Surgical Education: Results of An International Survey by The International Association of Student Surgical Societies (IASSS). (12th October 2021) - Kirby, E; Franco, H; Burger, S; Shadé Breedt, D; Davies, J; Azam, S; Weyers, J; Chan, K S
Abstract: Aim: Coronavirus disease 2019 (COVID-19) presents a variety of unforeseen challenges to medical students and surgical trainees. Adaptations to the content and delivery of medical education are inevitable as institutions respond to the virus. Departments face significant restructuring, with important implications for training. Our aim was to assess the global impact of the first wave of COVID-19 on medical and surgical education. Method: Between 12 May and 26 May 2020, an online survey was conducted and circulated to contacts of the International Association of Student Surgical Societies, including medical students and healthcare practitioners. All data were anonymous; no personal identifiable information was collected. Consent was implied by participation in the survey, which was on a voluntary basis. Results: We collated 527 responses from 111 institutions across 26 countries. Globally, 93.5% of medical student placements were affected by the first wave of COVID-19, with examination restructuring and alternative teaching methods employed by 87.8% of medical schools. Trainee redeployment was common in both surgical (61.5%) and non-surgical (77.1%) disciplines. Surgical services were significantly affected, with reduced elective procedures in 93% of institutions. On an individual level, COVID-19 resulted in prolonged absence from clinical duties and mental health concerns at all levels of training. Conclusions: Our data highlight drastic changes in medical and surgical education and practice as a result of the first wave of COVID-19. These changes are significant at all levels of training, both institutionally and individually. The pandemic is likely to have persistent consequences for future trainees in terms of education and career progression.